Simulation design based on piezoelectric photoelectric composite energy harvester. (1st March 2023) - Wang, Jieping; Song, Jiaming; Li, Shixiang; Liu, Hongmei; Dou, Yanwei
Abstract: A simulation design based on piezoelectric-photoelectric composite energy harvesters is proposed to solve the limitation that different energy harvesters can only work under certain conditions. The design of composite energy harvesting can capture sunlight and produce electrical energy and can also harvest vibrational energy in the environment to generate electricity from it. Cantilever beams with 6 different structures are simulated. The resonance frequency of the T-shaped cantilever beam is only 40 Hz, which can be used to collect vibration energy in the environment. The effect of different thicknesses of perovskite solar cells on the output performance was simulated. When the perovskite layer was 500 nm thick, the open circuit voltage could reach 1.08 V. The piezoelectric module and the photoelectric module are integrated into the energy collection circuit, which can collect vibration energy and light energy at the same time. The maximum output power may be obtained as 290 μW when the load resistance is 35 KΩ, and the output voltage at this time is 3.18 V. The structure broadens the application environment of the energy harvester and has the function of improving the output.